2018
DOI: 10.1016/j.apenergy.2017.12.121
|View full text |Cite
|
Sign up to set email alerts
|

Charge and discharge behavior of elemental sulfur in isochoric high temperature thermal energy storage systems

Abstract: In this work, a Monte Carlo model is used to investigate electron induced secondary electron emission for varying effects of complex surfaces by using simple geometric constructs. Geometries used in the model include: vertical fibers for velvet-like surfaces, tapered pillars for carpet-like surfaces, and a cage-like configuration of interlaced horizontal and vertical fibers for nano-structured fuzz. The model accurately captures the secondary electron emission yield dependence on incidence angle. The model sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 64 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The assumption of radial uniformity in the tube wall for any given axial location is valid due to its relatively low conductive thermal resistance [34]. While the storage medium does not exhibit radial uniformity, the convective heat transfer correlation given by Nithyanandam et al [35] provides an accurate measure of the volume averaged temperature within the storage medium and is used here. The thermophysical properties of sulfur, steel, and air are taken to be the average value for the temperature range considered using data from [34,36] and are given in Table 1.…”
Section: System Description and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of radial uniformity in the tube wall for any given axial location is valid due to its relatively low conductive thermal resistance [34]. While the storage medium does not exhibit radial uniformity, the convective heat transfer correlation given by Nithyanandam et al [35] provides an accurate measure of the volume averaged temperature within the storage medium and is used here. The thermophysical properties of sulfur, steel, and air are taken to be the average value for the temperature range considered using data from [34,36] and are given in Table 1.…”
Section: System Description and Assumptionsmentioning
confidence: 99%
“…The interstitial heat transfer coefficients are obtained from two different sources. The tube-side heat transfer coefficient is a function of the tube-side Rayleigh number and is obtained via an experimentally validated CFD model, the details of which can be found in the works of Nithyanandam et al [35]. For systems utilizing shell and tube style heat exchangers -which have analogous shell-side geometry to that of STTB -several studies have employed Kern's method [39], the Bell-Delaware method [40], and Wills-Johnson method [41] in order to quantify the shellside heat transfer coefficient and pressure drop.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Sulfur is promising storage medium, which can be used for thermal energy storage at high temperature with a lower cost, and has good charge-discharge performance at high temperature (Jin et al 2020;Nithyanandam et al 2018). As for the in uence of pyrite on CSC, studies have found that pyrite has a great in uence on low temperature oxidation in humid environment (Arisoy and Beamish 2015; Arisoy et al 2017).…”
Section: Introductionmentioning
confidence: 99%